MODEL KARTU MONITORING KADARZI TERHADAP PENINGKATAN STATUS GIZI BALITA - Vera T. Harikedua; Rudolf B. Purba; Muksin Pasambuna (Jurnal GIZIDO, 2017)
The Nutrition Awareness Family (KADARZI), is a family description of balanced nutrition behaviors, is able to recognize and solve the nutritional problems of its family members, besides it has good behavior in growth monitoring by taking into account the basic principles of child growth assessment including measuring the weight and length or height of children and comparing with growth standards. The purpose of growth assessment is to determine whether the child grows normally or has growth problems or there is a tendency to have growth problems that need to be addressed. Nutrition Research Assessment Results of Nutrition Status and Working Indicators of 2015, survey results show that for prevalence of under five nutrition status based on indicator of TB / U is very short prevalence age 0-23 months (6,5%) and short (13,1%) while in the national prevalence of very under five children (8.4%) and short toddlers (14.7%). The comparison between prevalence nationally compared with the province of North Sulawesi has a not too far away. Prevalence of nutritional status of children under 0-59 months based on national TB indicator (18.9%), North Sulawesi provincial prevalence (15.9%), while for North Minahasa district has prevalence (22.1%), with prevalence of provincial and national level hence categorized still high, (Kemenkes RI, 2016). The purpose of this research is to know the correlation between nutrient conscious family behavior with nutritional status of children under five in Likupang District of North Minahasa Regency.This type of research is observational with quasi experiment design. This research will analyze the effect of behavior change of nutritious family with the use of kadarzi monitoring card to five kadarzi indicators. The population in this study is all families who have children aged 0 - 5 years in the work area of Likupang Community Health Center, North Minahasa District.Conclusion there are 31,4% of research subjects mengalamin increase BB but from result of statistic test there is no change of behavior at monitoring weight of child of toddler (p> 0,05). Consumption of diverse foods that consume a complete 77.1%. Salt consumption is 100%. Toddlers who have not got exclusive breastfeeding 60%. Pregnant women who do not consume Fe 52.5%; 41.5% of puerperal mothers did not consume Vit A. Toddlers who consumed 86.7% vitamin A capsules and 55.1% red vitamin A. Suggestions To monitor KADARZI should use the available monitoring cards: Need to monitor with KADARZI card with a longer period of time to cover all components in monitoring Need to modify the simpler KADARZI card, making it younger and more practical in its use.